Kunstpreis der Böttcherstrasse in Bremen. - Kunsthalle, Bremen; Abegg, Georg; Ammann, Jean-Christophe; Heynen, Julian; Hofmann, Barbara; Hopfengart, Christine; Kahrs, Bringfriede; Kittelmann, Udo; Kurjakovic, Daniel; Loock, Ulrich; Montgomery, Robert; Stratman, Nicole; et al. (Bremen : Kunsthalle Bremen, 1995)
Armaly, Fareed ; Becker, Boris ; Doberauer, Anke ; Exner, Andreas ; Hamak, Herbert ; Höller, Stefan ; Kneffel, Karin ; Rondinone, Ugo ; Tillmans, Wolfgang ; Zakharov, Vadim ; Disler, Martin ; Bosslet, Eberhard ; Balkenhol, Stephan ; Lehnerer, Thomas ; Honert, Martin
biografie
Kunstpreis der Böttcherstrasse in Bremen, Kunsthalle Bremen, 15. Oktober bis 19. November 1995
Duits
boek